Vertical kinematic partitioning in intraplate fault systems: Evidence from the SE Korean Peninsula - Dieu-Veil Medry Hardy Nkodia; Francois Hategekimana; Sambit Prasanajit Naik; Youngbeom Cheon; Alexander L. Peace; Sang-Yeol Bae; Raj Sunil Kandregula; Young-Seog Kim (Journal of Structural Geology, 2026)

Evidence for distributed transpressional deformation and seismic hazard implications from the 2025 Mw 6.0 Asadabad- Kunar earthquake, Eastern Afghanistan - Afghanistan Hamedullah Torabi; Raj Sunil Kandregula; Sambit Prasanajit Naik; Zakeria Shnizai; Devanshu Ghildiyal; Vinay Singh Chufal; Young-Seog Kim (Natural Hazards, 2026)

Comprehensive surface level seismic hazard assessment for the state of Gujarat, India: implications for resilient infrastructure and communities - Madan Mohan Rout; Vinay Singh Chufal; Sambit Prasanajit Naik; Sumer Chopra; B. Sairam; Uday Bhan (Geosciences Journal, 2026)

Assessing the contemporary stress field and seismogenic structures of the Korean peninsula using focal-mechanism inversion and slip-tendency analysis - Dieu-Veil Medry Hardy Nkodia; Kiwoong Park; Sambit Prasanajit Naik; Alexander L. Peace; Young-Seog Kim (Tectonophysics, 2026)

A Comprehensive Review on Geoheritage Site of the Northwest Himalaya: a Special Emphasis on of Geological Significance, Conservation, and Geotourism Potential - Vinay Singh Chufal; Uday Bhan; Mohammed Irfan; Zahid Majid; Sambit Prasanajit Naik (Geoheritage, 2026)

Geosite Characterization and Evaluation of High-Altitude Alpine Lakes in the Kashmir Region, Northwest Himalaya, India - Mohammad Irfan; Ahsan Afzal; Simerjit Kaur; Sambit Naik; Saadat Saba; Kiran Sathunuri; Labeeb Gulzar (Geoheritage, 2026)

GNSS-derived TEC signatures of co-seismic ionospheric disturbances triggered by the Mw 7.6 Cayman Islands earthquake of 8 February 2025 - Sambit Prasanajit Naik; Siva Sai Kumar Rajana; Sampad Kumar Panda; Chiranjeevi G. Vivek; Devanshu Ghildiyal (Earth Science Informatics, 2026)

Seismo-ionospheric anomalies associated with the 2025 Mw 7.7 Myanmar earthquake: a case study - Siva Sai Kumar Rajana; Sambit Prasanajit Naik; Sampad Kumar Panda; Chiranjeevi G. Vivek; Sridevi Jade (Advances in Space Research, 2026)

Macroseismic intensity estimation based on earthquake environmental effects (EEEs) for the 2011 Tarlay earthquake, Myanmar: a case study from intraplate tectonic setting - Sambit Prasanajit Naik; Vinay Singh Chufal; Saw Ngwe Khaing; Myo Thant; Soe Thura Tun; Uday Bhan (Geosciences Journal, 2025)

Decoding paleostress conditions from the morphology of Quaternary volcanic craters along the western branch of the East African Rift System: implications for volcanic hazard assessment - Francois Hategekimana; Sambit Prasanajit Naik; Ho-Seok Choi; Yubi Oh; Digne Edmond Rwatangabo Rwabuhungu; Theophile Mugerwa; Young-Seog Kim (Bulletin of Volcanology, 2025)

Exploring the Geoheritage, Cultural Geomorphology, and Geotourism Potential of the Kashmir Region, Northwest Himalaya, India - Mohammad Irfan; Ahsan Afzal; Bikram Singh Bali; Savas Topal; Sambit Naik; Naseer Ahmad; Asif Bashir (Geoheritage, 2025)

Assessment of Active Deformation in the Surrounding Regions of the 7th to 12th AD Monuments in the Central Kumaon Himalayas: A Seismotectonic Approach using PSInSAR - Girish Ch. Kothyari; Achla Joshi; Rakesh K. Dumka; Bahadur S. Kotlia; Atul Kumar Patidar; Moulishree Joshi; Khayingshing Luirei; Sambit Prasanajit Naik; Ajay K. Taloor; Mayank Joshi; Hem Ch. Kothyari (Geoheritage, 2024)

Reconnaissance survey and macroseismic intensity estimation of the 26th May 2021 Gisenyi (Rwanda) earthquake (Mw 5.1) as a contribution to the seismic hazard assessment in a volcano-tectonic environment - Francois Hategekimana; Young-Seog Kim; Himanshu Mittal; Fils Vainqueur Byiringiro; Mohammed S. M. Adam; Digne Edmond Rwabuhungu Rwatangabo; Sambit Prasanajit Naik (Natural Hazards, 2024)

Geomorphological evidence inconvenient for the antecedent rivers of the Arun and Tista across the Himalayan range - Takashi Nakata; Yasuhiro Kumahara; Sambit Prasanajit Naik; Harutaka Sakai (Journal of Mountain Science, 2024)
The Arun and Tista Rivers, which flow across the Himalayas, are commonly known as antecedent valleys that overcame the rapid uplift of the Higher Himalayan ranges. To clarify whether the idea of antecedent rivers is acceptable, we investigated the geomorphology of the Himalayas between eastern Nepal and Bhutan Himalayas. The southern part of Tibetan Plateau, extending across the Himalayas as tectonically un-deformed glaciated terrain named as ‘Tibetan Corridor,’ does not suggest the regional uplift of the Higher Himalayas. The 8,000-m class mountains of Everest, Makalu, and Kanchenjunga are isolated residual peaks on the glaciated terrain composed of mountain peaks of 4,000–6,000 m high. The Tibetan glaciers commonly beheaded by Himalayan glaciers along the great watershed of the Himalayas suggest the expansion of Himalayan river drainage by glaciation. For the narrow upstream regions of the Arun and Tista Rivers with less precipitation behind the range, it is hard to collect enough water for the power of down-cutting their channels against the uplifting Himalayas. The fission track ages of the Higher Himalayan Crystalline Nappe suggest that the Himalayas attained their present altitude by 11–10 Ma, and the Arun and Tista Rivers formed deep gorges across the Himalayas by headward erosion.

Kinematic analysis and fault-dependence of building-wall fracture patterns during moderate earthquakes - Young-Seog Kim; Sambit Prasanajit Naik; Jin-Hyuck Choi; Kwangmin Jin; Gong-Ruei Ho; Taehyung Kim; Jinhyun Lee (Geosciences Journal, 2023)

Constraining mixing and mingling processes from zoned magmatic enclaves: An example from the Taejongdae granite in Busan, Korea - Mohammed S.M. Adam; Sung Won Kim; Taehyung Kim; Sambit Prasanajit Naik; Kyungo Cho; Young-Seog Kim (Lithos, 2023)

Signatures of 16th and 19th centuries paleo-earthquakes along the Himalayan Frontal Thrust (HFT), NW Himalaya, India: Implications to seismic hazard assessment - Javed N. Malik; Asmita Mohanty; Santiswarup Sahoo; Mahendrasinh S. Gadhavi; Mitthu Dhali; Shreya Arora; Sambit P. Naik (Quaternary International, 2023)

The earthquake environmental effects (EEEs) of the 6th February 2018, Hualien earthquake (Mw=6.4): A contribution to the seismic hazard estimation in the epicentral area - Sambit Prasanajit Naik; Asmita Mohanty; Himanshu Mittal; Sabina Porfido; Alessandro Maria Michetti; Benjamin Ming Yang; Ohsang Gwon; Young-Seog Kim (Quaternary International, 2023)

28th September 2018 Mw 7.5 Sulawesi Supershear Earthquake, Indonesia: Ground effects and macroseismic intensity estimation using ESI-2007 scale - Sambit Prasanajit Naik; Asmita Mohanty; Valkaniotis Sotiris; Himanshu Mittal; Sabina Porfido; Alessandro Maria Michetti; Ohsang Gwon; Kiwoong Park; Asri Jaya; Ryan Paulik; Chuanyou Li; Takahito Mikami; et al. (Engineering Geology, 2023)

First hand observations from the April 28, 2021 Sonitpur (MW 6.4) earthquake, Assam, India: possible mechanism involved in the occurrence of widespread ground effects - Mayank Joshi; Sambit Prasanajit Naik; Asmita Mohanty; Arun Bhadran; Drishya Girishbai; Swakangkha Ghosh (Geosciences Journal, 2023)

Generation of Liquefaction Potential Map for Kanpur City and Allahabad City of Northern India: An Attempt for Liquefaction Hazard Assessment - Sambit Prasanajit Naik; Nihar Ranjan Patra (Geotechnical and Geological Engineering, 2018)

Spatial Distribution of Shear Wave Velocity for Late Quaternary Alluvial Soil of Kanpur City, Northern India - Sambit Prasanajit Naik; Nihar Ranjan Patra; Javed N. Malik (Geotechnical and Geological Engineering, 2014)